Respuesta :

Answer:

A, C

Step-by-step explanation:

Quadratic formula:

[tex]x = \frac{ - b± \sqrt{b^{2} - 4ac } }{2a} [/tex]

a is the coefficient of x², b is the coefficient of x and c is the constant when a second degree polynomial is equal to zero. (ax² +bx +c= 0)

x² +5x +11= 0

a= 1, b= 5, c=11

Thus, using the quadratic formula:

[tex]x = \frac{ - 5± \sqrt{ {5}^{2} - 4(1)(11)} }{2(1)} \\ x = \frac{ - 5± \sqrt{25 - 44} }{2} \\ x = \frac{ - 5± \sqrt{ - 19} }{2} [/tex]

∴The answers are A and C.

ACCESS MORE